2006
DOI: 10.1111/j.1574-695x.2006.00151.x
|View full text |Cite
|
Sign up to set email alerts
|

Potential prophylactic value of bovine colostrum in necrotizing enterocolitis in neonates: anin vitrostudy on bacterial attachment, antibody levels and cytokine production

Abstract: Necrotizing enterocolitis (NEC) is an important disease of low birth-weight neonates. The immaturity of the gut mucosa may result in close contact between the host epithelium and microorganisms which are normally confined to the gut lumen. Damage of the mucosa due to endotoxin, cytokine production or other factors is believed to then occur. The aim of this study was to determine whether spray-dried bovine colostrum demonstrated potential in vitro as a prophylactic for NEC. Antiadherence was measured using a ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 30 publications
1
28
1
3
Order By: Relevance
“…In this study, it was shown that BC decreased the levels of serum pro-inflammatory cytokines. This result is in contrast to the result of Brooks et al 9 from an in vitro study performed with cells. These differences may be thought to result from the differences be-…”
contrasting
confidence: 86%
See 2 more Smart Citations
“…In this study, it was shown that BC decreased the levels of serum pro-inflammatory cytokines. This result is in contrast to the result of Brooks et al 9 from an in vitro study performed with cells. These differences may be thought to result from the differences be-…”
contrasting
confidence: 86%
“…The reason is that endotoxin release is not correlated with the severity of SIRS and that, practically, intestinal ischemia generated secondarily by hemorrhage alone without detectable endotoxins is known to increase cytokine gene expression. 9,37 In summary, our results show that BC may have beneficial effects in treating and preventing intestinal barrier damage, bacterial translocation, and the relevant SIRS and MODS in the intestinal I/R-injured rat model.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…It is unknown if therapeutic regimens that reduce inflammatory cytokines and the associated mucosal responses of infants with NEC (34 -37) will improve nutrient absorption. The lower incidence and severity of NEC in the CC pigs may be related to colostrum reducing the secretion of inflammatory cytokines by gut epithelial cells and decreasing bacterial adherence (38). The present study did not include pigs given formula during PN and converted to colostrum for EN, as this was not considered a clinically relevant treatment.…”
Section: Discussionmentioning
confidence: 99%
“…BC proved to have beneficial effects on NEC development and intestinal function in a piglet model and these data were confirmed by an in vitro study in which a modulatory action of colostrum proteins in cytokines secretion from bacteria-stimulated murine bone marrowderived dendritic cells was observed (170). An in vitro study suggested that pretreatment with BC significantly reduced several bacteria specie (Enterobacter cloacae, Klebsiella oxytoca, Escherichia coli, Serratia marcescens and Klebsiella pneumonia) in attachment to HT-29 cells, although the treatment increased the levels of some proinflammatory cytokines (171). Intestinal function was restored by BC administration after initial formula-induced inflammation in a pig model of NEC.…”
Section: Necrotizing Enterocolitis (Nec)mentioning
confidence: 69%